Propidium Monoazide based selective iDNA monitoring method improves eDNA monitoring for harmful algal bloom Alexandrium species - Yun, Kun-Woo; Son, Hwa-Seong; Seong, Min-Jun; Kim, Mu-Chan (Frontiers in Marine Science, 2023)
eDNA, also known as environmental DNA, has garnered significant attention due to its potential applications in various fields such as biodiversity assessment, species distribution monitoring, ecological interaction analysis, and quantitative analysis. However, the presence of non-selective DNA signals in eDNA samples poses challenges in accurately detecting species, assessing biodiversity, and conducting quantitative analysis. To address these limitations, this study developed a novel method for selectively detecting iDNA from specific species in eDNA samples. The method involved the application of PMA treatment to Alexandrium spp. effectively preventing the detection of non-selective exDNA signals. Additionally, by optimizing the filter size used in the sampling process, the researchers were able to selectively collect and analyze iDNA from species of interest, particularly Alexandrium spp. Furthermore, the study successfully demonstrated the selective collection and analysis of iDNA from Alexandrium spp. cysts present in the sediment layer, further strengthening the findings. The results indicated that the combined use of PMA treatment and filter size optimization significantly enhanced the selective detection capability of iDNA. The successful selective detection of iDNA from eDNA in the sediment layer highlights the practical applicability of the developed method. This study holds promise for advancing eDNA monitoring technology by providing a selective iDNA detection method utilizing PMA. Moreover, these findings lay the foundation for effectively utilizing iDNA in environmental conservation, monitoring, and ecological research.